2020
DOI: 10.21438/rbgas(2020)071713
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência de Anadenanthera colubrina (Vell.) Brenan (angico) no semiárido da Paraíba, Nordeste do Brasil

Abstract: A presente pesquisa objetivou registrar e analisar a distribuição e disponibilidade de Anadenanthera colubrina (Vell.) Brenan em oito comunidades rurais no semiárido da Paraíba. Foram realizados levantamentos registrando todos os indivíduos com diâmetro no nível do solo (DNS) igual ou superior a 3 cm, utilizando os métodos de coletas das parcelas, ponto quadrante e caminhamento livre. Nos parâmetros fitossociológicos para o método de parcelas registrou-se DeR de 0,04 a 4,2, FrR de 0,21 a 9,33, e VI de 0,27 a 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In addition, they also observed that this situation is mainly linked to anthropic action, since the growth of A. colubrina was greater in the center of the plots, where it had less anthropic influence. According to Anselmo et al (2020), the values found may vary depending on the area studied, from a protected area to a modified one, in addition, another factor must also be taken into account, which is the relationship between people and the species, which may be affecting the occurrence of the same.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…In addition, they also observed that this situation is mainly linked to anthropic action, since the growth of A. colubrina was greater in the center of the plots, where it had less anthropic influence. According to Anselmo et al (2020), the values found may vary depending on the area studied, from a protected area to a modified one, in addition, another factor must also be taken into account, which is the relationship between people and the species, which may be affecting the occurrence of the same.…”
Section: Results and Conclusionmentioning
confidence: 99%